Essential oils from Inula japonica and Angelicae dahuricae enhance sensitivity of MCF-7/ADR breast cancer cells to doxorubicin via multiple mechanisms. (2nd March 2016) - Wu, Min; Li, Tingting; Chen, Lilan; Peng, Sugang; Liao, Wei; Bai, Ruolan; Zhao, Xue; Yang, Hong; Wu, Chunhui; Zeng, Hongjuan; Liu, Yiyao
Abstract: Ethnopharmacological relevance: Angelicae dahurica (Hoffm.) Benth. & Hook.f.ex Franch. & Sav combined with Pueraria and Gastrodia elata Bl. combined with Inula japonica Thunb. are widely used in herb-pairs of traditional chinese medicine. Previous studies have shown that Angelicae dahuricae essential oil (ADO) enhanced puerarin internalization into ABCB1-overexpressed Caco-2 cells. These findings suggest the possibility that essential oils may enhance the absorption via certain mechanisms related to ABCB1 and reverse multidrug resistance (MDR). Aim of the study: ADO and essential oils from Inula japonica (IJO) may reverse ABCB1-mediated MDR, but this ability has not been investigated in detail in the well-established cancer cell lines. In this study, the underlying molecular mechanisms were further investigated to examine how IJO and ADO reverse MDR in the resistant human breast cancer cell line of MCF-7/ADR. Also this work may help uncover the conceivable compatibility mechanisms of above herb-pairs involved in ABCB1. Materials and methods: The MDR human breast cancer MCF-7/ADR cells were treated with IJO, its sesquiterpene component isoalantolactone (ISO) or ADOat non- cytotoxic concentrations. The MDR ability was examined by measuring the sensitivity to doxorubicin (DOX), DOX accumulation and efflux, ABCB1 ATPase activity, ABCB1 expression, membrane fluidity, and stability and localization of lipid rafts and caveolae. Finally, the molecular modeling was performed to postulate how ISO interacts with ABCB1. Results: Treating MCF-7/ADR cells with IJ oil, ISO or AD oil reversed MDR 2- to 3-fold, without affecting the sensitivity of the non-MDR parental cell line. Mechanistic studies showed that these oils down-regulated mRNA and protein expression of ABCB1, and reduced the stability of lipid rafts in the cell membrane, which has previously been shown to reduce ABCB1-mediated transport. On the other hand, IJO, ISO and ADO did not inhibit ABCB1 ATPase activity, and fluorescence polarization experiments showed that low concentrations of the oils did not appear to alter membrane fluidity, unlike some MDR-reversing agents, ISO showed a higher docking score than verapamil but lower than dofequidar and tariquidar. Conclusions: Our results suggest that IJO, ISO and ADO could reverse MDR by down-regulating ABCB1 expression and reducing lipid raft stability. These findings may be useful for developing safer and effective MDR reversal agents and also help find out the compatibility mechanisms. Graphical abstract: In this work, we found IJO, ISO and ADO could reverse multidrug resistance (MDR) in the breast cancer cell line MCF-7/ADR, and also explored the molecular mechanisms by molecular modeling analysis. These three oils could down-regulate the expression of ABCB1 in both mRNA and protein level, and reduce the stability of lipid rafts in the cell membrane. However, the three oils didn't affect ABCB1 ATPase activity and membrane fluidity at low concentrations. Our findings demonstrated that these three oils could reverse MDR by down-regulating ABCB1 expression and reducing lipid raft stability.